Long-Term Patency of Stent Angioplasty for Aortoiliac Occlusive Disease: A Literature Review - Siagian, Ira H; Utama, Alexander J (UI Scholars Hub, 2024)
Introduction. Surgical revascularization remains a definitive therapy for aortoiliac occlusive disease. Revascularization could be achieved via endovascular treatment using angioplasty or open surgery. A limited number of studies currently assess the long-term patency of stent angioplasty of aortiliac occlusive disease. This study aims to evaluate or find recent evidence regarding the evaluation of the long-term patency of stent angioplasty for the treatment of aortoiliac occlusive disease. Method. Literature searching was conducted through several online databases, including Cochrane, PubMed, and EBSCOHost. Several cohort and randomized controlled studies assessing long-term patency of stent angioplasty ranging from bare metal stent to balloon angioplasty published from 2010 to 2022 were included. Critical appraisal was conducted using the Oxford Centre of Evidence-Based Medicine checklist. Results. Initial database searching yielded 26 published titles, of which 21 were excluded based on our inclusion-exclusion criteria and being a duplicate. Five studies, consisting of five cohort studies and one systematic review, were included. Long-term primary, assisted-primary, and secondary patency data were acquired in each study. Conclusion. We found heterogeneous data regarding long-term patency in each study. We found that 60-month primary patency ranges from 74.7% - 83.9%, assisted primary patency ranges from 83.7% - 95.8%, and secondary patency ranges from 92.8% - 99%. Overall, endovascular therapy by angioplasty has proven satisfactory long-term patency over five years.